Meningkatkan Keterampilan Mengajar Guru Dengan Manajemen Kelas - Yusuf, Zulfikar; Anisatu Thoyyibah (Jurnal Pengabdian UntukMu NegeRI, 2022)
The purpose of this activity is to produce educators who have competence in managing classes. By forming a paradigm as an educator, Knowing the characteristics of the students, and being able to make good planning and organizing in class management, all through public speaking, class management, and other things related to teaching. The dedication uses the andragogy approach which will lead to a two-way thinking process that uses various techniques, with training, simulation, and presentation. This relates to the strengthening of human resources from the internal "Strengthening of the Heart", and the external side of the skills of an educator. The skills to be trained are skills in the field of public communication and the diversity of approaches, models, strategies, methods and teaching techniques. The results of the dedication show that the dialogical process that is built is able to make reflection for every teacher to live the profession as a teacher. In terms of classroom management skills, teachers already have an understanding of strategies, models, methods and media. As for the media, the teachers produce media work that can be used in the learning process in the classroom.